Identification and expression analysis of the ZF-HD gene family in castor - XU Xingyuan; HUANG Fenglan; ZHANG Chunlan; ZHU Mengyang; CUI Zhiyu; LIU Peng (Xibei zhiwu xuebao)
[Objective] The ZF-HD family genes of castor were identified and analyzed by sequence analysis, phylogenetic analysis, promoter and expression pattern analysis, to provide a reference for further study of the function of ZF-HD genes in castor. [Methods] Based on the whole genome data of castor, ZF-HD genes were identified, and bioinformatics and expression analysis under abiotic stress were carried out. [Results] A total of 13 ZF-HD genes were identified from castor, which were unevenly distributed on Chr1-Chr10. All 13 RcZF-HD proteins were hydrophilic unstable proteins, and were localized in the nucleus. The RcZF-HD genes were clustered into three subgroups, and the number of genes in each group was different. The gene structure was conserved within the group but diversified between groups. RcZF-HD genes had a large number of tissue-specific elements, stress response elements, and hormone response elements. The ZF-HD genes were widely responsive to abiotic stresses and their expression was tissue-specific. [Conclusion] A total of 13 ZF-HD genes were identified in castor. It is known that members of the castor ZF-HD gene family play an important role in responding to abiotic stress, this research provides theoretical basis for the study of castor􀆳s stress resistance.